Influence Of Cognitive Processes On The Learning Of Young Schoolchildren - L. S. Tursunov (Genius Journals, 2025)
This article, dedicated to the influence of reason on a child's cognitive development, as well as the role of knowledge in acquiring knowledge, pays special attention to the mental ontogenesis of primary school children.
Keywords: Mind; non-intelligence; contemplation; perception